A Facile Synthesis of Stable Heterocyclic Phosphorus Ylides - Javad Sabounchei, Seyyed; Karami, Kazem (Asian Journal of Chemistry, 2016)
Stable crystalline phosphorus ylides are obtained from 1 : 1 : 1 addition between tertiary phosphine, dialkyl acetylenedicarboxylate and strong N––H acids, such as imidazole or benzimidazole. These compounds were identified by FTIR, FTNMR and elemental analysis.